A Hand-On Approach: Review of Tom Tyler, Ciferae: A Bestiary in Five Fingers - Traisnel, Antoine (Humanimalia, 2013)
Tom Tyler, Ciferae: A Bestiary in Five Fingers. Minneapolis: University of Minnesota Press, 2012. 319 pp. 30 pbk.